Human cytomegalovirus: a survey of end-organ diseases and diagnostic challenges in solid organ transplant recipients. Issue 4 (August 2022) - Contreras, Gustavo; Ho, Dora
Abstract : Purpose of review: Human cytomegalovirus (CMV) infection is one of the most important infectious complications in solid organ transplant (SOT) recipients, leading to significant morbidity and mortality. Therefore, early detection and prompt treatment are imperative to improve transplant outcomes. This article highlights the clinical characteristics of the most common CMV end-organ diseases in SOT recipients and their diagnostic modalities and challenges. Recent findings: CMV can cause a variety of end-organ diseases in SOT recipients. Although CMV nucleic acid amplification by polymerase chain reaction (PCR) is frequently employed to detect CMV reactivation or infection, its predictive value for various CMV end-organ diseases remains uncertain. Given the limitation of PCR or other noninvasive tests, confirmation of CMV end-organ disease may require tissue biopsy, which may not be feasible or available, or may cause untoward complications. Summary: The utility of PCR to diagnose CMV end-organ disease is limited. As CMV can infect any organ system(s), clinicians caring for SOT recipients need to maintain vigilance for any signs and symptoms of end-organ disease to allow early recognition and prompt treatment. Invasive procedures might be needed to confirm the diagnosis and minimize the empirical use of antiviral therapy that may have substantial drug toxicities.